On the thermodynamic behavior of cadmium in Te-saturated HgTe-CdTe and CdSe-CdTe solid alloys - Shamsuddin M.; Nasar A. (My University, 2025)
The activity of cadmium in Te-saturated HgTe-CdTe and CdSe-CdTe alloys in the temperature range of 720 to 840 K was measured by an electrochemical technique using LiCl-KCl + 5 wt pct CdCl2 as the molten salt electrolyte. From the electromotive force (emf), values measured at different temperaturesi the partial and excess molar thermodynamic quantities, viz., Δ G Cd M, Δ G Cd XS, Δ H Cd M, Δ S Cd M and Δ S XS Cd, have been calculated. From the activity data, the equilibrium vapor pressure of cadmium over the alloys have been estimated. The thermodynamic data obtained in the present investigation are consistent with the view that the HgTe-CdTe system consists of a single-phase field throughout the entire range of composition and with the structural changes in the CdSe-CdTe system. The results have been discussed in the light of Darken's stability and excess stability parameters of the systems and physical properties, viz., energy gap and magnetic susceptibility. © 1995 The Minerals, Metals & Material Society.